Competencia cultural de psicólogos en su práctica clínica con mujeres transgénero. - López Pérez, Doren Miguel (My University, 2025)
Introduction: Psychological care for transgender women in Latin America faces limitations due to prejudices and insensitive practices. Objective:To characterize clinical psychologists' perceptions of their cultural competence in caring for transgender women. Methodology: Exploratory qualitative study with semi-structured interviews of 15 psychologists, interpretative phenomenological analysis using MAXQDA. Results: Fragmentation was evident in the awareness, knowledge and skills dimensions of Sue's model, with cognitive predominance without practical application. Conclusions: Cultural competence is structurally deficient, requiring specific training programs and institutional response
Introducción: La atención psicológica a mujeres transgénero en Latinoamérica enfrenta limitaciones por prejuicios y prácticas poco sensibles. Objetivo: Caracterizar las percepciones de psicólogos clínicos sobre su competencia cultural en la atención a mujeres transgénero. Metodología: Estudio cualitativo exploratorio con entrevistas semiestructuradas a 15 psicólogos clínicos, análisis fenomenológico interpretativo mediante MAXQDA. Resultados: Se evidenció fragmentación en las dimensiones awareness, knowledge y skills del modelo de Sue, con predominio cognitivo, pero sin aplicación práctica. Conclusiones: La competencia cultural es estructuralmente deficiente, requiriéndose programas formativos específicos y respuesta institucional.
Keywords: COMPETENCIA CULTURAL; LATINOAMÉRICA; PSICOLOGÍA; PSICOTERAPIA